2000
DOI: 10.1086/317619
|View full text |Cite
|
Sign up to set email alerts
|

Serum Antibody as a Marker of Protection against Natural Rotavirus Infection and Disease

Abstract: To determine whether naturally acquired serum IgA and IgG antibodies were associated with protection against rotavirus infection and illness, a cohort of 200 Mexican infants was monitored weekly for rotavirus excretion and diarrhea from birth to age 2 years. Serum samples collected during the first week after birth and every 4 months were tested for anti-rotavirus IgA and IgG. Children with an IgA titer >1:800 had a lower risk of rotavirus infection (adjusted relative risk [aRR], 0.21; P<.001) and diarrhea (aR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
120
1
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(134 citation statements)
references
References 38 publications
7
120
1
6
Order By: Relevance
“…Similarly, Velazquez et al showed that the incidence of any type of rotavirus infection is generally highest among infants 6-14 months old and decreases in children 21-23 months old. They also reported a high incidence of reinfection which, however, usually is mild [30]. Accordingly, only one of 607 children in our case series was hospitalized twice for RV gastroenteritis.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Similarly, Velazquez et al showed that the incidence of any type of rotavirus infection is generally highest among infants 6-14 months old and decreases in children 21-23 months old. They also reported a high incidence of reinfection which, however, usually is mild [30]. Accordingly, only one of 607 children in our case series was hospitalized twice for RV gastroenteritis.…”
Section: Discussionmentioning
confidence: 70%
“…Studies of the disease burden of RV conducted in Europe and the USA have included retrospective studies of diarrheal hospitalization [8,13,28], laboratory-based studies [28,30], reviews of published and unpublished data [18,25], and analyses of cost effectiveness [29]. Data about RV morbidity in Europe are available mainly for southern [2,9,26], northern [16,31], and western parts [1,3,6,11,28].…”
Section: Introductionmentioning
confidence: 99%
“…21 In addition, these findings advocated the idea that an attenuated vaccine causing asymptomatic infection can induce protective immunity. 24 Taking this into consideration, it is suggested that two doses of RIX4414 mimics the degree of protection against RV GE that follows an asymptomatic natural infection.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution and magnitude of antibodysecreting cell (ASC) and memory B cell responses to virulent (Vir) human rotavirus (HRV) Wa strain (P1A [8]G1), the attenuated (Att) Wa HRV or the combined vaccine regimen of AttHRV oral priming followed by 2/6-virus-like particle (2/6VLP) intranasal (IN) boosting (AttHRV-2/6VLP) have been delineated in our previous studies of gnotobiotic (Gn) pigs [2][3][4][5][6]. The protective role of rotavirus-specific IgA effector and memory B cells in intestinal lymphoid tissues and IgA antibodies in the serum, intestinal contents or feces against rotavirus diarrhea have been indicated in the Gn pig model of HRV diarrhea [3,[5][6][7][8] and in studies of rotavirus natural infection of humans [9][10][11]. In humans, serum IgA and sometimes IgG antibody titers were correlated with protection after rotavirus natural infection [12]; but not after vaccination with Rotashield™ [9,13], implying a potential role for other effectors including T cell mediated immunity in the protection induced by this tetravalent reassortant rotavirus vaccine.…”
Section: Introductionmentioning
confidence: 99%